APPLICATION OF INTERACTIVE POWER POINT LEARNING MEDIA ON MATHEMATICAL FRACTIONS IN CLASS IV ELEMENTARY SCHOOL 32 LUBUKLINGGAU - Vina Enjeli (Teaching and General Education Studies, 2025)
This study investigates the effectiveness of interactive PowerPoint as a learning medium to improve mathematics learning outcomes on fractional material among fourth-grade students at SD Negeri 32 Lubuklinggau. The research was motivated by low student achievement in understanding fractions, which are often perceived as abstract and complex. Traditional teaching methods have contributed to reduced student interest and participation, prompting the need for a more engaging and innovative approach. A quantitative method with a pre-experimental one-group pre-test and post-test design was employed. The participants were 10 fourth-grade students. Data were collected using multiple-choice tests administered before and after the intervention, as well as observation sheets to assess student engagement. Gain score analysis was used to measure improvement in learning outcomes. The results showed a substantial increase in student performance, with the average pre-test score rising from 37.5 to 87.5 on the post-test. The gain score of 0.82 indicates a high level of improvement. Observations also revealed greater interest and active participation during lessons using interactive PowerPoint. These findings imply that interactive digital media can effectively enhance students’ conceptual understanding and motivation. Further research is recommended to explore long-term retention and the integration of other technology-based learning strategies.